Retroperitoneal Leiomyoma in a Man Under Feminization Therapy: A Rare Case Report - Solis-Tun, Nidia Naomi; Vivas-Baizabal, Marco G.; Bolado-García, Patricia B.; González-Medina, Wendy E.; Cigarroa-Galicia, Octavio; Inclán-Figueroa, Heriberto; Mijangos-Vergara, Fernando A.; Alcántara-Dzib, Jose R.; Guzmán-Jaramillo, Rogelio (British Journal of Healthcare and Medical Research, 2025)
Retroperitoneal leiomyomas are rare, benign, hormone-sensitive tumors that are particularly uncommon in male patients. This report presents the case of a 41-year-old male undergoing feminization therapy, who was diagnosed with a retroperitoneal leiomyoma associated with Denonvilliers’ fascia. Imaging studies revealed a large, solid, homogeneous mass with characteristics resembling muscular tissue, maintaining clear interfaces with the surrounding structures. Immunohistochemical analysis identified spindle-shaped cells positive for smooth muscle actin and estrogen receptors. This case contributes to the limited literature on retroperitoneal leiomyomas in male patients, highlighting the potential association between feminization therapy and tumor development or accelerated growth and underscoring the need for further research in this area.